2018
DOI: 10.1016/j.neuron.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Cells and Circuits of Touch in Normal and Pathological Settings

Abstract: The sense of touch is fundamental as it provides vital, moment-to-moment information about the nature of our physical environment. Primary sensory neurons provide the basis for this sensation in the periphery; however, recent work demonstrates that touch transduction mechanisms also occur upstream of the sensory neurons via non-neuronal cells such as Merkel cells and keratinocytes. Within the spinal cord, deep dorsal horn circuits transmit innocuous touch centrally and also transform touch into pain in the set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(126 citation statements)
references
References 172 publications
3
123
0
Order By: Relevance
“…2; in particular, TNX-deficient mice exhibited increased sensitivity to innocuous mechanical stimuli but not to noxious thermal stimuli. The perception of acute noxious heat stimuli is typically initiated by unmyelinated C fibers and thinly myelinated Aδ fibers, and in turn induces nociceptive responses 19,20 . Sensing of innocuous tactile stimuli is mainly conducted through myelinated Aβ fiber, which have fast conduction velocities and low activation thresholds.…”
Section: Hypersensitization Of A-fiber In Tnx −/− Micementioning
confidence: 99%
“…2; in particular, TNX-deficient mice exhibited increased sensitivity to innocuous mechanical stimuli but not to noxious thermal stimuli. The perception of acute noxious heat stimuli is typically initiated by unmyelinated C fibers and thinly myelinated Aδ fibers, and in turn induces nociceptive responses 19,20 . Sensing of innocuous tactile stimuli is mainly conducted through myelinated Aβ fiber, which have fast conduction velocities and low activation thresholds.…”
Section: Hypersensitization Of A-fiber In Tnx −/− Micementioning
confidence: 99%
“…; Moehring et al. ) to correlate neurophysiological with neurochemical properties. Here we report on the basic electrophysiological properties of 535 superficial lamina I/II TNc neurons acquired through whole‐cell patch‐clamp recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies characterizing the electrophysiological properties of TNc laminae I/II neurons defined four cell types exhibiting a tonic, phasic, or delayed action potential (AP) firing pattern, but also single-spiking neurons (Sedlacek et al 2007;Davies and North 2009;Alba-Delgado et al 2015). While studies in the dorsal horn of the spinal cord found that firing pattern does not always correlate well with inhibitory or excitatory cell identity (Yasaka et al 2010), the use of cre-dependent fluorescent reporter mouse lines has been shown to be especially useful Punnakkal et al 2014;Alba-Delgado et al 2015;Peirs et al 2015;Cheng et al 2017;Moehring et al 2018) to correlate neurophysiological with neurochemical properties. Here we report on the basic electrophysiological properties of 535 superficial lamina I/II TNc neurons acquired through whole-cell patch-clamp recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Projection neurons make up less than 10% of all dorsal horn neurons, while more than 90% of the neuronal population are interneurons of which, between 60 and 70% are excitatory glutamatergic neurons, and the rest is inhibitory (GABA and/or glycinergic).The spinal cord is organized in a laminar fashion, which has initially been proposed on the basis of differences in cell density and morphology between the different laminae [4, 5] but has later been shown to also reflect functional organization. This is especially reflected for example by the lamina specific innervation pattern by the different types of peripheral sensory neurons: unmyelinated C fibers, which mainly carry noxious and thermal information, terminate in the superficial dorsal horn (laminae I-II), while thickly myelinated Ab fibers, which convey innocuous signals including touch and proprioceptive information, terminate in the deep dorsal horn (laminae III-V) [3,6,7]. A laminar organization of neuronal function is also supported by gene expression patterns that follow laminar patterns [8][9][10][11][12].…”
mentioning
confidence: 99%
“…A laminar organization of neuronal function is also supported by gene expression patterns that follow laminar patterns [8][9][10][11][12]. Furthermore, optogenetic and chemogenetic experiments support a modality-specific processing by distinct genetically defined neuron populations [7,[13][14][15]. However, the cellular basis of this modality specific processing and hence the identity of interneuron types is only incompletely understood.…”
mentioning
confidence: 99%